2022
DOI: 10.3389/fimmu.2022.836939
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Synthase Is the Key Regulator of Fatty Acid Metabolism and Is Related to Immunotherapy in Bladder Cancer

Abstract: Fatty acid metabolism (FAM) genes are potentially useful for predicting prognosis and immunotherapy response in bladder cancer (BC). To examine this, we constructed a prognostic model and identified key FAM genes in BC. Using transcriptional expression profiles and clinical data of BC patients from public datasets and Changhai (CH) hospital, we built and validated a risk-score model based on 13 prognostic FAM genes. Differential gene expression identified fatty acid synthase (FASN) as central to fatty acid met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Besides, lipid pathways which included arachidonic acid, α-linolenic acid, linoleic acid, and fatty acid metabolism were all more dynamic in the low TMMSscore group. One study highlighted that fatty acid metabolism was an important intermediate in lipid metabolism, was involved in the origin and evolution of several metabolic diseases and cancers, while this study also highlighted that fatty acid synthase took on a critical signi cance in BC fatty acid metabolism and could be a potential target for immunotherapy 39 . Another study reported that tyrosine kinases in tyrosine metabolism regulated the cell growth process through different signaling pathways such as growth, migration, differentiation and metabolism and had the potential to become a personalized anti-cancer therapeutic regimen 40 .…”
Section: Discussionmentioning
confidence: 93%
“…Besides, lipid pathways which included arachidonic acid, α-linolenic acid, linoleic acid, and fatty acid metabolism were all more dynamic in the low TMMSscore group. One study highlighted that fatty acid metabolism was an important intermediate in lipid metabolism, was involved in the origin and evolution of several metabolic diseases and cancers, while this study also highlighted that fatty acid synthase took on a critical signi cance in BC fatty acid metabolism and could be a potential target for immunotherapy 39 . Another study reported that tyrosine kinases in tyrosine metabolism regulated the cell growth process through different signaling pathways such as growth, migration, differentiation and metabolism and had the potential to become a personalized anti-cancer therapeutic regimen 40 .…”
Section: Discussionmentioning
confidence: 93%
“…In bladder cancer, FASN is a key regulator of fatty acid metabolism and is associated with immunotherapy. In addition, immune analysis showed that FASN was significantly associated with several immune cells ( 52 ). Another enzyme, HSD17B4, is also involved in the synthesis and elongation of unsaturated fatty acids ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…The liver, as the core site of lipid metabolism, plays a vital role in the lipid cycle [ 25 ]. FAS, CACT, and ACC all contribute to the control of lipid synthesis [ 39 , 40 , 41 ]. In our study, FAS, CACT, and ACC activity were down-regulated by Aurantiochytrium sp.…”
Section: Discussionmentioning
confidence: 99%